In community in Christ: a study of theological setting of the sacraments in the New Testament - Moore, Basil S (Rhodes University, Faculty of Divinity, Department of Divinity, 1971)
Introduction: Neville Clark has rightly warned against the attempt to approach the theology of the sacraments from a broad and general definition of a 'sacrament' from which we 'read off' a Christian doctrine of the sacraments without paying due regard to the biblical statements. Such an approach could not but obscure the essential differences between the sacraments, and the fact that they stem from historical roots. On the other hand, the specialist treatment of the sacraments which begins by making a detailed analysis of the biblical material fails to do justice to the wholeness of biblical theology and tends to treat the sacraments in isolation not only from each other but also from other aspects of Christian theology with which they are inalienably connected. Bearing in mind the difficulties inherent in both of these approaches, a fresh and more systematic approach is required.
Keywords: Sacraments; Sacraments (Liturgy)